Analysis of Blood Pressure, Proteinuria, and Hemoglobin Levels in Preeclampsia Patients - Atikah Dinda Ramadhani Mahmud; Rasfayanah; Pratiwi Nasir Hamzah; Masita Fujiko M. Said; Gina Isni Djanuaresty Iskandar (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2026)
Background: Preeclampsia is a leading global cause of maternal and perinatal mortality, marked by hypertension and proteinuria after 20 weeks of gestation. High blood pressure triggers endothelial dysfunction and renal impairment, while changes in hemoglobin levels often indicate disease severity. Analyzing these clinical parameters is vital for assessing organ involvement in patients. Purpose: This study aimed to analyze the association between blood pressure, proteinuria level, and hemoglobin concentration among preeclamptic patients at St. Khadijah 1 Hospital Makassar. Methods: This analytical observational study employed a cross-sectional design using secondary data obtained from medical records of 51 preeclamptic patients during January–December 2024. Patients were classified into preeclampsia and severe preeclampsia based on blood pressure severity, with severe hypertension defined as systolic ≥160 mmHg and/or diastolic ≥110 mmHg. Data included blood pressure, dipstick proteinuria results, and hemoglobin concentration. The Chi-Square test was used to assess the relationship between variables, with a significance level of p<0.05. Results: Most patients experienced severe preeclampsia (54.9%), had proteinuria grade 2 or higher (56.9%), and had normal hemoglobin levels (80.4%). A significant association was found between blood pressure and proteinuria (p=0.003). However, no significant association was observed between blood pressure and hemoglobin concentration (p=0.740). Conclusion: Blood pressure is significantly associated with proteinuria in patients with preeclampsia, suggesting a potential role in renal endothelial dysfunction. In contrast, hemoglobin concentration does not exhibit a significant relationship with blood pressure. Regular monitoring of blood pressure and proteinuria remains critical for assessing disease progression and informing timely interventions in preeclampsia.